Patient-related factors predicting the failure of mandibular osteosynthesis. Issue 1 (January 2022) - Sarai, Rupinder; Wu, Eiling; Ahmed, Asad; Williams, Rhodri; Breeze, John
Abstract : Introduction : Patients that do not comply with post- operative instructions are at higher risk of failure following mandibular fixation. However, anticipating those patients who will not comply is challenging and may lead to the incorrect choice of mandibular fixation type. Our aim was to identify those patient-related factors, that if known pre- operatively, may either potentially be modified or can be used to assist in the determination of which method of osteosynthesis is employed. Methods : All adult patients who underwent plate fixation of their mandible fractures in the symphysis to angle regions between 01 October 2018 and 01 June 2021 were retrospectively identified. The odds of developing post- operative complications and requiring a return to theatre were determined for different patient-related factors and methods of plate fixation. Results : Of 337 fractures treated using load sharing principles, 27/337 (8.01%) developed complications and 20/337 (5.93%) required a return to theatre (RTT) for repeat osteosynthesis. Of 74 fractures treated using load-bearing principles, 7/74 (9.46%) developed complications and 2/74 (2.70%) required a return to theatre for repeat osteosynthesis. In patients with known substance misuse, the odds of the patient needing to return to theatre was significantly higher for those that underwent load sharing osteosynthesis than load bearing osteosynthesis (p = 0.048, OR = 0.152, CI: 0.024–0.953). Conclusions : This analysis found that of those patient-related factors, known substance misuse has a higher risk of return to theatre and would suggest that fractures in such patients should be primarily treated by load-bearing fixation.